Desarrollo de un sistema de supervisión de los parámetros eléctricos de un banco de motores basado en IOT. - Jami Jami, Byron Rodrigo (2023)
This technological project entitled "Development of an IoT-Based Electrical Parameter Monitoring System for a Motor Bank" has as its main objective to address the advantage provided by the monitoring of variables present in electric motor banks through the implementation of Internet of Things (IoT) technologies. The central problem that was solved with this project is the importance of maintaining a value of 0. 92 of power factor in a bank of electric motors to guarantee its efficiency and useful life, as well as to avoid costly penalties dictated by regulatory agencies such as ARCONEL, for this 5 variables were identified which are voltages, currents, power factor, frequency and powers, the same that change depending on the loads (resistive, capacitive and inductive) applied, it is worth mentioning the creation of a graphical interface in LabVIEW software where the behavior of each of them is shown and the development of a manual of laboratory practices. To develop the IoT system, a Wecon V-Box router was used, which is designed to build a system that encompasses the internet of things in the industrial field in a safe and reliable way, using the latest connectivity technologies to achieve communication between the modules, and a SCADA cloud interface was created for real-time monitoring that gives access to the activation of loads remotely from a cell phone or a conventional computer as well as the generation of historical data, which the system stores for a period of 60 days.